Urea Adsorption By Activated Carbon Derived From Oil Palm Kernel Shell And Empty Fruit Bunch Fiber - Ooi , Chee Heong (2014)
The present hemodialysis treatment is expensive and seriously affects the life of a patient due to its low effectiveness and efficiency in uremic toxin removal. Thus, nanoporous materials are needed to improve the treatment. Palm kernel shell (PKS) and empty fruit bunch (EFB) fiber biomass from palm oil mills can be utilized to synthesize low cost nanoporous activated carbon (AC) which can be applied in artificial kidney system for urea adsorption. In this study, granular activated carbon (GAC) was synthesized from PKS via different carbonization temperatures and durations as well as the sulfuric acid (H2SO4) treatment. Activated carbon fiber (ACF) was derived from EFB via the treatment with different acid impregnation ratios followed by the carbonization and CO2 gas activation at 900°C. The physical and chemical properties of the samples were studied. Increase of carbonization temperatures from 400 to 600°C resulted in the increase in urea adsorption predominantly due to increase in surface area. The increase of carbonization duration from 3 to 6 hours improved surface area but does not improve urea adsorption. Instead, C-H functional group is the main factor that influences urea adsorption. The H2SO4 treatment enhances surface area of GAC sample and eventually improves the urea adsorption. The optimum condition for the synthesis of ACF sample with excellent pore characteristic is the acid treatment at 1.5 acid-to-EFB fiber ratio. Further increase of the ratio reduces the surface area due to excess water vaporization via H2SO4 dehydration. Regardless of the obtained surface area, increase of acid impregnation ratio deteriorates the urea adsorption by ACF samples due to the decrease in C-H surface functional groups. Overall, the presence of C-H surface functional group in AC was proven the vital factor for higher urea adsorption capacity.